A biological perspective on differences and similarities between burnout and depression. (February 2017) - Orosz, Ariane; Federspiel, Andrea; Haisch, Sarie; Seeher, Christian; Dierks, Thomas; Cattapan, Katja
Highlights: Contrasting burnout and depression promises directions for treatment approaches. Burnout and depression are discussed on the basis of biological correlates of stress. An index based on the combination of various parameters should be elaborated. Abstract: To compare and contrast burnout and depression is not only a conceptual issue, but may deliver important directions for treatment approaches and stabilize the awareness of disease which is essential for affected individuals. Because of the symptomatic overlap, it is a subject of multidimensional research and discussion to find specific signatures to differentiate between the two phenomena or to present evidence that they are different aspects of the same disorder. Both pathologies are regarded as stress-related disorders. Therefore, in this review burnout and depression are discussed on the basis of biological parameters, mainly heart rate variability (HRV) and brain-derived neurotrophic factor (BDNF), which are crucial to the stress response system. It emerges that instead of finding one specific discriminating marker, future research should rather concentrate on elaborating indices for burnout and depression which integrate combinations of parameters found in genetics, neurobiology, physiology and environment.